The Strategic Role of Indonesian Ulama in the Global Dissemination of Islamic Values through Islamic English - Hisan, Lana Choerotun; Triyoko, Hanung (Journal of Language and Literature Studies, 2025)
This study explores the strategic role of Indonesian ulama in disseminating Islamic values to global audiences through the use of Islamic English. In an era marked by increasing interreligious tensions and the need for cross-cultural dialogue, Islamic English has emerged as a vital medium for conveying the principles of peace, tolerance, and compassion to both Muslim and non-Muslim audiences worldwide. The research focuses on two main questions: (1) how Indonesian ulama utilize Islamic English to promote Islamic values, and (2) what strategies are employed to foster interfaith harmony and religious diplomacy. Employing a qualitative library research method with content analysis, the study examines a range of sources including speeches, sermons, publications, and interfaith programs. The findings indicate that Indonesian ulama use Islamic English not only to translate Islamic concepts, but to bridge cultural and linguistic gaps in interreligious communication. Digital platforms such as YouTube and social media have also expanded the ulama’s reach and impact. Initiatives like the “English for Ulama” program exemplify Indonesia’s soft-power approach in positioning moderate Islam globally. Through strategic use of language and engagement in interfaith dialogue, Indonesian ulama contribute to shaping a global discourse on Islam that emphasizes harmony over conflict. This research concludes that Islamic English is a powerful tool for religious diplomacy and plays a crucial role in promoting Indonesia’s image as a peaceful and democratic Muslim-majority nation.